COMMISSION TRIALS OF THE MANUFACTURING TECHNOLOGY, AND PHYSICAL AND IMMUNOBIOLOGICAL PROPERTIES, OF A NOVEL LIVE MODIFIED COLD-ADAPTED VIRAL VACCINE AGAINST EQUINE INFLUENZA - Tabynov , K.K.; Assanzhanova , N.N.; Ryskeldinova , Sh.Zh.; Kozhamkulov , Y.M.; Inkarbekov , D.A.; Kydyrbayev , Zh. (Eurasian Journal of Applied Biotechnology, 2016)
We developed a novel live modified viral vaccine for specific prophylaxis of equine influenza virus subtype H3N8, based on the reassortant cold-adapted strain, A/HK/Otar/6:2/2010. Previously we performed all stages of vaccine development, from a battery of laboratory studies, to isolating the vaccine strain, up to evaluation of vaccine safety and effectiveness in horses. The next important step is to summarise the laboratory studies and to confirm compliance of the properties of the developed vaccine with the requirements (specification) of the normative and technical documentation (NTD) draft for vaccine preparation. The results of this study will determine the potential for use of the vaccine in compliance with the NTD for approval by the authorized state body in the field of veterinary medicine. The process of manufacturing and quality control of the finished vaccine was carried out in accordance with an approved program, which was based on the draft NTD for the vaccine. The studies demonstrated that a laboratory series of vaccine (13,400 vials or 134,000 doses), prepared according to the developed methodology, met the requirements of the draft NTD completely with regards to quality parameters including appearance, the presence of impurities, vacuum, solubility, pH, mass fraction of humidity, sterility, infectious activity, safety and immunogenicity. The vaccine, therefore, withstood the commission trials. The results of these commission trials of a novel live modified cold-adapted viral vaccine against equine influenza will subsequently be presented for agreement and approval, according to the draft NTD.Keywords: equine influenza, vaccine, cold-adapted strain, normative and technical documentation, physical properties, safety, immunogenicity, commission trials.